El comercio de Alicante en los reinados de Felipe II y Felipe III: una construcción desde la cooperación - Montojo Montojo, Vicente (Cuadernos de Historia Moderna, 2007)
The commerce of Alicante in the reign of Philip II, studied from the perspective of its social group, has been analysed from fiscal sources of Alicante, (the book of the ’sisa’,- a type of tax- of merchandise of 1565), judicial documents of Valencia (the proceedings of the Royal Audience, and the orders and embargoes of civil justice in Valencia), and notarial contracts of Castille (protocols of Cartagena and Yecla), which complicated the activity of the Alicante merchants, and at the same time reveals their secrets to us. This business had a large Italian component, from Genova, Milan and Florence, and a lesser imput from France and Valencia, but within a framework of cooperation, of family relations and enoblement. So, although the commentator Viciana stated that Alicante attracted merchants from Cartagena and also Italy, it has been shown that this was not so, except for a few who did so in 1570, as Cartagena also received Italian emigrants, whose merchants had good relations with those of Alicante, as it was demonstrated in times of epidemics that they were able to halt maritime traffic. Alicante obtained a privileged fiscal position in its access to the southern Castillian plateau (the southern Customs houses), and this greatly favoured its commerce, on top of being occupied with the provision of Valencia and other centres, such as the interior of Valencia.